The Impact of Macroeconomic Factors on the IHSG, with Stock Prices as an Intervening Variable - Dody Admiral Iskandar; Muh. Ashary Anshar; Andi Faisal Syam (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the effects of exchange rates and inflation on the Composite Stock Price Index (IHSG), with LQ45 stock prices as an intervening variable, for the period 2021–2025. Research Method: This study employs a quantitative approach using monthly secondary data obtained from the Indonesia Stock Exchange, Bank Indonesia, and the Central Statistics Agency. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through path analysis and bootstrapping procedures using SmartPLS. Results and Discussion: The results show that the exchange rate has a positive effect on the LQ45 Stock Price and the IHSG, whereas inflation does not affect either variable. The LQ45 Stock Price has a positive effect on the IHSG and partially mediates the exchange rate's effect on the IHSG, but does not mediate the relationship between inflation and the IHSG. Implications: These findings underscore the importance of exchange rate stability as a foundation for investment decision-making and the formulation of capital market policies. Originality: The novelty of this study lies in testing the mediating role of the LQ45 stock price in explaining the transmission mechanism by which macroeconomic variables affect the IHSG.